Macular Bruch’s membrane defect and dome-shaped macula in high myopia - Fang, Yuxin; Jonas, Jost B. (PLOS ONE, 2017)
To examine an association between macular Bruch’s membrane defects (MBMD) and a dome-shaped appearance of the macula (DSM).